Accretion of Uranus and Neptune: Confronting different giant impact scenarios - Esteves, Leandro [UNESP]; Izidoro, André; Winter, Othon C. [UNESP] (Elsevier, 2025)
The origins of Uranus and Neptune are not fully understood. Their inclined rotation axes – obliquities – suggest that they experienced giant impacts during their formation histories. Simulations modeling their accretion from giant impacts among ∼5 Earth masses planetary embryos – with roughly unity impactors’ mass ratios – have been able to broadly match their current masses, final mass ratio, and obliquity. However, due to angular momentum conservation, planets produced in these impacts tend to rotate too fast, compared to Uranus and Neptune. One potential solution for this problem consists of invoking instead collisions of objects with large mass ratios (e.g. a proto-Uranus with 13 M⊕ and an embryo of 1 M⊕). Smooth-particle hydrodynamics simulations show that in this scenario final planets tend to have rotation periods more consistent with those of Uranus and Neptune. Here we performed a large suite of N-body numerical simulations modeling the formation of Uranus and Neptune to compare these different dynamical views. Our simulations start with a population of protoplanets and account for the effects of type-I migration, inclination and eccentricity tidal damping. Our results show that although scenarios allowing for large impactors’ mass ratio favor slower rotating planets, the probability of occurring collisions in these specific simulations is significantly low. This is because gas tidal damping is relatively less efficient for low-mass embryos (≲1 M⊕) and, consequently, such objects are mostly scattered by more massive objects (∼13 M⊕) instead of colliding with them. Altogether, our results show that the probability of broadly matching the masses, mass ratio, and rotation periods of Uranus and Neptune in these two competing formation scenarios is broadly similar, within a factor of ∼2, with overall probabilities of the order of ∼0.1%–1%.
Keywords: Neptune; Origin; Planetary dynamics; Planetary formation; Solar system; Uranus